Different Effects of Numerical Magnitude on Visual and Proprioceptive Reference Frames - Blini, Elvio; Cattaneo, Zaira; Vallar, Giuseppe (Frontiers in Psychology, 2013)
This study assessed whether numerical magnitude affects the setting of basic spatial coordinates and reference frames, namely the subjective straight ahead. Three tasks were given to 24 right-handed healthy participants: a proprioceptive and a visuo-proprioceptive task, requiring pointing to the subjective straight ahead, and a visual task, requiring a perceptual judgment about the straight ahead position of a light moving left-to-right, or right-to-left. A control task, requiring the bisection of rods of different lengths, was also given. The four tasks were performed under conditions of passive auditory numerical (i.e., listening to small, “2”, and large, “8”, numbers), and neutral auditory-verbal (“blah”) stimulation. Numerical magnitude modulates the participants’ deviations in the visual straight ahead task, when the movement of the light is from left to right, with the small number bringing about a leftward deviation, the large number a rightward deviation. This result suggests that the spatial effects induced by the activation of the mental number line extend to an egocentric frame of reference. A similar directional modulation was found in the rod bisection task, in line with previous evidence. No effects of numerical magnitude were found on the proprioceptive and visuo-proprioceptive straight ahead tasks. These results suggest that the spatial effects induced by the activation of the mental number line extend to an egocentric frame of reference but only when a portion of horizontal space has to be “actively” explored.